PENGARUH FINANCIAL BEHAVIOR DAN FINANCIAL SELF-EFFICACY TERHADAP MANAJEMEN KEUANGAN PRIBADI MAHASISWA PROGRAM STUDI S1 PENDIDIKAN AKUNTANSI FEB UNESA - Mokhammad Dimas Baihaqi; Rohayati, Suci (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Personal financial management is an important skill for students to meet their needs during college and to prepare for future financial conditions. However, students still experience difficulties in managing their finances due to consumptive behavior, lack of financial planning, and low confidence in their financial management ability. This study aims to analyze the effect of financial behavior and financial self-efficacy on the personal financial management of undergraduate students of the Accounting Education Study Program, Class of 2022, Faculty of Economics and Business, Universitas Negeri Surabaya. This quantitative study used a causal approach with a saturated sampling technique involving 105 respondents. Data were collected through a Likert-scale questionnaire and analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression with IBM SPSS Statistics version 25. Hypotheses were tested using t-test, F-test, and the coefficient of correlation and determination (R and R2). The results show that financial behavior has a significant effect on personal financial management, financial self-efficacy has a significant effect on personal financial management, and both variables simultaneously have a significant effect on personal financial management. The better the financial behavior and the higher the students’ self-efficacy in managing finances, the better their personal financial management.